Less-Affected Hand Function in Children With Hemiparetic Unilateral Cerebral Palsy: A Comparison Study With Typically Developing Peers. (October 2017) - Rich, Tonya L.; Menk, Jeremiah S.; Rudser, Kyle D.; Feyma, Timothy; Gillick, Bernadette T.
Background . Neurorehabilitation interventions in children with unilateral cerebral palsy (UCP) target motor abilities in daily life yet deficits in hand skills persist. Limitations in the less-affected hand may affect overall bimanual hand skills. Objective . To compare hand function, by timed motor performance on the Jebsen-Taylor Test of Hand Function (JTTHF) and grip strength of children with UCP to children with typical development (CTD), aged 8 to 18 years old. Exploratory analyses compared hand function measures with regard to neurophysiological outcomes measured by transcranial magnetic stimulation and between group comparisons of hemispheric motor threshold. Methods . Baseline hand skills were evaluated in 47 children (21 UCP; 26 CTD). Single-pulse transcranial magnetic stimulation testing assessed corticospinal tract and motor threshold. Results . The mean difference of the less-affected hand of children with UCP to the dominant hand of CTD on the JTTHF was 21.4 seconds (95% CI = 9.32-33.46, P = .001). The mean difference in grip strength was −30.8 N (95% CI = −61.9 to 0.31, P = .052). Resting motor thresholds between groups were not significant, but age was significantly associated with resting motor threshold ( P < .001; P = .001). Children with UCP ipsilateral pattern of motor representation demonstrated greater mean differences between hands than children with contralateral pattern of motor representation ( P < .001). All results were adjusted for age and sex. Conclusions . The less-affected hand in children with UCP underperformed the dominant hand of CTD. Limitations were greater in children with UCP ipsilateral motor pattern. Rehabilitation in the less-affected hand may be warranted. Bilateral hand function in future studies may help identify the optimal rehabilitation and neuromodulatory intervention.